Higher Serum Brain-Derived Neurotrophic Factor Levels Are Associated With a Lower Risk of Cognitive Decline: A 2-Year Follow Up Study in Community-Dwelling Older Adults - Fujiwara, Yoshinori; Ihara, Kazushige; Hachisu, Mitsugu; Suzuki, Hiroyuki; Kawai, Hisashi; Sakurai, Ryota; Hirano, Hirohiko; Chaves, Paulo H. M.; Hashizume, Masahiro; Obuchi, Shuichi (Frontiers in Behavioral Neuroscience, 2021)
Objective To assess the relationship of serum brain-derived neurotrophic factor (BDNF) levels with the subsequent short-term decline in cognitive functioning in community-dwelling older adults. Design Two-year prospective, observational study. Setting and Participants The study included 405 adults aged 65–84 years, initially free of a dementia diagnosis who were living in Tokyo, Japan. Methods Participants underwent health assessments at baseline (2011) and follow-up (2013). Serum BDNF levels and scores from the Montreal Cognitive Assessment-Japanese version (MoCA-J) were systematically measured. Logistic regression was used to estimate the odds of cognitive decline between baseline and follow-up assessments in the full MoCA-J scale (operationally defined as a decrease of two or more points), as well as in MoCA-J subscales (decline of one or more points in a specific subscale), as a function of serum BDNF level, adjusting for baseline demographics, prevalent chronic diseases, and baseline cognitive scores. Results Among individuals who performed worse on the full MoCA-J at baseline (i.e., scores in the bottom quartile [≤21], which is consistent with a mild cognitive impairment status), but not among those who performed better (top 3 quartiles), those with highest baseline serum BDNF levels (top quartile) had lower odds of subsequent decline in the full MoCA-J scale than those with lowest (bottom quartile); i.e., odds ratio (OR): 0.10 (95% confidence interval [CI]: 0.02–0.62; p = 0.013). Regarding MoCA-J subscales, adjusted odds of decline in the executive function subscale, but not in the other five subscales, were substantially low among those with highest baseline serum BDNF levels (top quartile), as compared to those with the lowest (bottom quartile), i.e., OR: 0.27 (95% CI:0.13–0.60; p < 0.001). Conclusion and Implications Higher serum BDNF levels were associated with a lower risk of decline in cognitive function in a sample of community-dwelling older Japanese adults. Risk varied across cognitive subdomains and according to baseline cognition. This warrants further research to evaluate the added-value of serum BDNF in health promotion initiatives directed toward cognitive decline prevention in community-dwelling older adults.